Caribbean Report 14-03-1991 - Goffe, Leslie (anchor); Ransome, Debbie (correspondent); Garth, Hugh (correspondent); Williams, Eddie (correspondent); Binnendijk, Chandra van (correspondent); Cox, Sheila (interviewee); Nuffield, Ed (interviewee); Ninvalle, Pete (correspondent) (The British Broadcasting Corporation, 1991)
The political crisis continues in Antigua and a report is provided on the current state of events as the Deputy Prime Minister delivers an emotional speech in Parliament. Preparations for the May 25th elections is in progress in Suriname. However, there seem to be a lack of interest by members of the population as the voter registration is not significant. A Canadian Member of Parliament, Jim Karygiannis appears to be fighting for his own political life when he returns to Canada after a week long visit to Trinidad and Tobago. Mr. Karygiannis. He has stated that his reason for the visit to Trinidad and Tobago was on behalf of its citizens who were seeking refugee status in Canada due to discrimination faced by the government of Trinidad and Tobago. There is hope for greater economic development in the Caribbean when the free trade bloc between the United States, Canada and Mexico finally comes into effect. Such development is likely to take place in tourism and imports into the Caribbean.
1. Headlines (00:00 – 00:27)
2. This segment provides an update on the political crisis in Antigua. Lester Bird, the Deputy Prime Minister, delivers an emotional speech in Parliament and gives the reasons for calling his father, Prime Minister Vere Bird Snr. to retire. He said he rejected his father’s feeble attempt to present a budget in its correct legal form as it caused him great concern. He warned the six MPs who have joined him to stand firm with their position to support the call for the retirement of Dr.. Bird. It appears that there will be a new cabinet tomorrow and Vere Bird Jnr., the disgraced son of the Prime Minister, will be appointed as a member of the cabinet (00:28 – 03:08)
3. An update from Suriname is provided as preparations for the May 25 elections is in progress. The interim government has launched a nationwide campaign calling for citizens to register to vote in the upcoming elections as the deadline for registration draws close. To date only 10% of the population has responded to the call due to their disappointment with the performance of the last government. There seems to be a lack of interest in the upcoming elections (03:09 – 05:07)
4. This segment provides an update on the oil slick that occurred in St. Maarteen, St. Barts and other islands in the Caribbean. It appears that it has practically disappeared and the beach front residents are involved in cleaning up activities. However, patches of oil are still in the coastal waters and residents are not letting their guard down. They have established contacts with many agencies in the event that there is need to call for expert assistance (05:08 - 07:07)
Keywords: Antigua -- economic conditions.; Antigua -- Politics and government.; Suriname -- Politics and government.; Elections -- Suriname.; Political campaigns -- Suriname.; Refugees -- Trinidad and Tobago.; Discrimination -- Trinidad and Tobago.; Canada -- Politics and government.; Oil spills -- Caribbean area.; Economic development -- Caribbean area.; Bird, Vere Cornwall, 1909-1999.; Karygiannis, James "Jim"; Bird, Lester Bryant.; Liberal Party, Canada.